Promoting the spirit of nationalism through Quran-Hadis lectures: A case of Gus Miftah’s da'wah model - D. I. Ansusa Putra; Ardiyansyah Ardiyansyah; Mekki Klaina (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The idea of nationalism as the national glue in Indonesia faces currents of decadence in contemporary society. As a religious text, the Quran and Hadith and their interpretations have a special role in stemming this decadence of nationalism through the teachings of preachers, preachers and preachers. Gus Miftah, as a well-known preacher in Indonesia, tries to promote the spirit of nationalism by contextualizing messages and values from the Quran and Hadith with the conditions of diversity and multiculturalism in Indonesia. This article raises Gus Miftah as a popular preacher with a high commitment to issues of nationality and Indonesianness. This study uses a qualitative descriptive method in analyzing digital observation data on Gus Miftah's video lectures on Youtube. This study resulted in a general conclusion that Gus Miftah's Quran-Hadith Teaching contextualizes the Quran-Hadith within the framework of nationalism and diversity. Gus Miftah's commitment to the national interest issue can be seen from his understanding of socio-religious themes, such as tolerance, unity and nationalism. This is a factor in the popularity of Gus Miftah's da'wah which is in line with traditional/moderate Islamic understanding. This research contributes to enriching the literature on the relationship between da'wah and contextualization of the Quran and Hadith in Indonesia which gives rise to a uniqueness of Indonesian Islam. ***Gagasan nasionalisme sebagai perekat bangsa di Indonesia menghadapi dekadensi dengan isu-isu kontemporer masyarakat. Sebagai teks agama, Al-Quran dan Hadits serta tafsirnya memiliki peran khusus dalam membendung dekadensi nasionalisme ini melalui ajaran para da'i, muballigh, atau ulama. Gus Miftah, sebagai seorang mubaligh ternama di Indonesia, mencoba mengangkat semangat nasionalisme dengan mengkontekstualisasikan pesan dan nilai-nilai dari Al-Qur'an dan Hadits yang sejalan dengan kondisi kebhinekaan dan multikulturalisme di Indonesia. Artikel ini mengangkat Gus Miftah sebagai pendakwah populer dengan komitmen tinggi terhadap isu tersebut. Penelitian ini menggunakan metode deskriptif kualitatif dalam menganalisis data observasi digital pada video ceramah Gus Miftah di Youtube. Kajian ini menghasilkan kesimpulan umum bahwa Gus Miftah mengontekstualisasikan ajaran Al-Qur'an-Hadits dalam kerangka nasionalisme dan kebinekaan. Komitmen Gus Miftah terhadap isu kepentingan nasional tampak dalam pemahamannya terhadap tema-tema sosial keagamaan, seperti toleransi, persatuan, dan nasionalisme. Hal ini menjadi faktor popularitas dakwah Gus Miftah yang sejalan dengan pemahaman Islam tradisional/moderat. Penelitian ini berkontribusi untuk memperkaya literatur tentang hubungan dakwah dan kontekstualisasi Alquran dan Hadits di Indonesia yang memunculkan keunikan Islam Indonesia.